Indigenous Islamic Multiculturalism: Interreligious Relations in Rural East Java, Indonesia - Umam, Fawaizul; Barmawi, Mohamad (Ulumuna, 2023)
This research-based article discusses interreligious relations and religious believers’ views as determining forms of interreligious relations. It chose a village in a rural area as the research locus, namely Sukoreno, Jember Regency, East Java Province. This village has four religious communities (Islam, Hinduism, Christianity, Catholicism) and one mysticism community (Sapta Darma). So far, they have displayed a peaceful-productive relationship amid the cultural diversities, especially religious differences. This is interesting in Indonesia's current situation, which is often plagued by religious conflicts. It is also important in the context of multiculturalism discourse, which tends to be urban-biased and its enrichment in an Islamic perspective. Therefore, this study explores forms of interreligious relations and how the Sukoreno community uses them as cultural energy to build social cohesion. From an Islamic perspective, the findings can be used as a pilot model for multicultural Indonesian society, both in rural areas and urban areas, where demographically, the majority of citizens are Muslims. Moreover, interreligious relations in Sukoreno can prove that Indonesian people have the cultural wealth to build their own multiculturalism, rooted in the cultural treasures of their own locality, indigenous Islamic multiculturalism.